43.0k views
2 votes
Simplify the expression (3 – 3i)3 by performing operations with pure imaginary numbers and complex numbers. (Provide an explanation as I am terrible at calculus and need major assistance, thanks!)

A) –27 + 216i

B) –27 + 54i

C) –54 – 216i

D) –54 – 54i

User MetaGuru
by
5.6k points

1 Answer

6 votes

Answer:

D

Explanation:

Given:
z=3-3i

Find:
z^3=(3-3i)^3

Solution:

Use the formula


(a-b)^3=a^3-3a^2b+3ab^2-b^3

Hence,


(3-3i)^3\\ \\=3^3-3\cdot 3^2\cdot(3i)+3\cdot 3\cdot (3i)^2-(3i)^3\\ \\=27-81i+9\cdot 9i^2-3^3i^3\\ \\=27-81i+81i^2-27i^3

Now remind that


i^2=-1,

then


i^3=i^2\cdot i=-1\cdot i=-i

Substitute:


(3-3i)^3\\ \\=27-81i+81\cdot (-1)-27\cdot (-i)\\ \\=27-81i-81+27i\\ \\=27-81-81i+27i\\ \\=-54-54i

User Camille
by
5.1k points